Changing occupations or changing companies : predictors of different types of premature contract terminations in dual vocational education and training programs - Stefanie Findeisen [Verfasser]; Lukas Ramseier [Verfasser]; Neuenschwander, Markus P. [Verfasser] (My University, 2024)
„In Switzerland, access to non-academic occupations requires the completion of a vocational education and training (VET) program. Over two-thirds of adolescents choose to start a dual VET program after compulsory education. However, this path from school to work is not always linear, and changes can be a means of adjusting wrong career choices. In the context of dual VET, two types of adjustments that occur frequently can be distinguished: (1) change of occupations and (2) change of companies. The present study aims to examine the predictors of each of those two types of changes. First, we are interested in the link between individuals’ intentions to change their career paths and actual changes. When changes are intended by the trainee and aimed at correcting wrong career choices, actual changes can generally be expected to be predicted by change intentions. Second, we are interested in the role of person-job ft (P-J ft) as well as trainees’ socialization and performance indicators. Third, we examine to what extent trainees’ decisions to change occupations or companies can be predicted by pre-entry factors (perceived P-J ft and efort during compulsory education before the transition to VET). We used a longitudinal sample of adolescents at the end of compulsory school and at the end of their frst year in a dual VET program in Switzerland. This data set is combined with government data on actual changes regarding individuals’ training companies and their occupations. The two types of adjustments were examined in separate structural equation models that compared trainees without any types of adjustments during their training program (1) to those who changed occupations (N=417) and (2) to those who changed training companies (N=378). The results show that actual occupational changes and actual company changes of trainees are afected by the same work-context predictors (negative efect of trainees’ self-perceived work performance) and pre-entry predictors (negative efect of efort during compulsory education). However, in contrast to changes of training companies, changes of occupations are signifcantly predicted by trainees’ intentions to change. Moreover, while P-J ft during the VET program is the only direct predictor of trainees’ intentions to change occupations, intentions to change companies are not signifcantly predicted by P-J ft. Intentions to change companies are negatively afected by companies’ socialization tactics and positively afected by adolescents’ pre-entry efort. Overall, the results call for a more diferentiated assessment of changes/ premature contract terminations in future studies. Whether change intentions are a valid proxy for actual change behavior seems to depend on the type of changes that trainees decide to make.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 2.4.4 Biografiegestaltung; 370; Berufsausbildung; Berufsentscheidung; Arbeitsplatzwechsel; Ausbildungswechsel; Berufswechsel; Einflussfaktor; Berufliche Mobilität; Schweiz